Engaged scholarship and civic responsibility in higher education - Burton, Sharon L., 1960- (Hershey, PA : IGI Global, 2018)
'This book addresses the various stages of engaged scholarship - nonexistent, transitioning, middle, fully implemented, and maintenance to include the difficulties and challenges. It addresses different aspects of engaged scholarship adoption: the usage and implementation of social media, implementation and coordination of technologies to drive engaged scholarship, learning and development required, funding required for engaged scholarship'--
Higher education out-of-the-box : technology driven learning innovation in higher education / Miltiadis Lytras, Paraskevi Papadopoulou, Christina Marouli, Anastasia Misseyanni -- Telemedicine and telehealth : academics engaging the community in a call to action / Kim Brown-Jackson -- Empowering civic responsibility : Insights from service learning / Miftachul Huda, Kamarul Azmi Jasmi -- Financial literacy education program-post financial housing crisis : community based financial literacy education program / Shanel Lu -- Connecting concepts of self-efficacy, engaged scholarship, and civic responsibility among student-veterans / Shaneen Dials-Corujo -- Digital engaged scholarship rethinking scholarly practices in the age of distance, online, and hybrid education : transforming secondary and higher education by retrofitting proactive solutions / Dustin Bessette -- Collaboration : academes, government, and community to drive economic uplift and empowerment / Christopher Alan Bullock -- Driving STEM through engaged scholarship and civic responsibility / Yoshino W. White.
Includes bibliographical references.
Keywords: Civics -- Study and teaching (Higher); Service learning